Dual‐protected amino acid derivatives as new antitubercular agents. (31st May 2018) - de Castro, Pedro P.; Campos, Débora L.; Pavan, Fernando R.; Amarante, Giovanni W.
Abstract : Tuberculosis is an infectious disease with high incidence and growing drug‐resistant rates. In an attempt to develop new antitubercular agents, 35 compounds were synthesized, most of them bearing a carbamate and enantiopure amino acid moiety. These compounds had their activity evaluated toward a Mycobacterium tuberculosis strain (ATCC 27294) and cytotoxicity against fibroblast MRC‐5 cells (ATCC CCL‐171). Three of the prepared derivatives presented a good antimicrobial inhibition and two of them a moderate cytotoxicity. The lipophilicity seems to play a vital role in the cell growth activity, with best results for the derivatives with a higher logP. Abstract : Efficient synthesis and antitubercular evaluation of dual‐protected amino acid derivatives, containing a lipophilic chain, carbamate, and amino acid moieties. Besides the high yields of the products, one of the most lipophilic compounds showed 5 μm inhibition against M. tuberculosis .